Dual usage toilet bowl / Bakri Ali - Ali, Bakri (Universiti Teknologi MARA, Kedah, 2019)
Toilet bowl are used worlwide and each house may use 2 or 3 of it. Normal toilet bowl are either sitting type or squatting type. Modern houses normally use a sitting type since the squatting type is regarded as old fashioned. For the public toilets, normally both types are used. This will requires many toilets has to be built and of course using more space and increased cost. Recently there is a study claiming a squatting toilet is better for our health. This is also true according to Islamic teaching where the believers are taught to squats when pooping or peeing. However in some circumstances like for disable, elderly and people with hips and knee problems, squatting is a big problem. Using a sitting bowl as a squatting toilet is prohibited due to safety and cleanliness. This new innovation 2 in 1 toilet bowl considered all people and can be used either for sitting or squatting without any problem. Therefore all toilet can be fixed with this “DUAL” toilet bowl thus reducing the space as well as the cost for public toilet and the needy dont have to check the type of bowl in every toilet before using it.